Riddle of the rusty horseshoe - Quill, Penumbra (My little pony. Ponyville mysteries, 2017)
Join the Cutie Mark Crusaders--Sweetie Belle, Apple Bloom, and Scootaloo--as they read mysteries, legends, ghost stories, and every other kind of tale that makes a mane stand on end.